2021
DOI: 10.1007/s12542-021-00582-7
|View full text |Cite
|
Sign up to set email alerts
|

Habitability of the early Earth: liquid water under a faint young Sun facilitated by strong tidal heating due to a closer Moon

Abstract: Geological evidence suggests liquid water near the Earth’s surface as early as 4.4 gigayears ago when the faint young Sun only radiated about 70% of its modern power output. At this point, the Earth should have been a global snowball if it possessed atmospheric properties similar to those of the modern Earth. An extreme atmospheric greenhouse effect, an initially more massive Sun, release of heat acquired during the accretion process of protoplanetary material, and radioactivity of the early Earth material hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 93 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…where T eq is equilibrium temperature, A is albedo, L e is solar luminosity, σ is the Stefan-Boltzmann constant, and a is the semimajor axis of the planet. Luminosities for the Sun at 4.4 bya (0.705 L e ) and 4.0 bya (0.728 L e ) are obtained from a precomputed stellar evolution model of a Sun-like star (Heller et al 2020;Baraffe et al 2015). The Hadean Earth would have been mostly covered in water; therefore, albedo is taken to be 0.06, which is consistent with a cloudless water world (Roesch et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where T eq is equilibrium temperature, A is albedo, L e is solar luminosity, σ is the Stefan-Boltzmann constant, and a is the semimajor axis of the planet. Luminosities for the Sun at 4.4 bya (0.705 L e ) and 4.0 bya (0.728 L e ) are obtained from a precomputed stellar evolution model of a Sun-like star (Heller et al 2020;Baraffe et al 2015). The Hadean Earth would have been mostly covered in water; therefore, albedo is taken to be 0.06, which is consistent with a cloudless water world (Roesch et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We compute two habitable P-T profiles for each model by slightly adjusting the methane content and/or surface pressure. The luminosity, UV intensity, and asteroid bombardment rate at each epoch are based on stellar evolution models (Heller et al 2020;Baraffe et al 2015), observations of solar analogs (Ribas et al 2005), and the lunar cratering record (Chyba 1990), respectively.…”
Section: Complete Impact-atmosphere-ocean Coupling Modelsmentioning
confidence: 99%
“…The increase of greenhouse gas contents, such as CO 2 and CH 4 , is likely responsible for the faint young Sun problem (FYSP) (e.g., Byrne & Goldblatt, 2014; Le Hir et al., 2014; Wolf & Toon, 2013; Wordsworth & Pierrehumbert, 2013). Other factors or feedbacks may have also contributed to solving this problem, such as a different atmospheric pressure, a less continent coverage, N‐H 2 collision‐induced warming, and a stronger tidal heating induced by the closer Moon (Goldblatt & Zahnle, 2011; Goldblatt et al., 2009; Heller et al., 2021; Rosing et al., 2010; Wordsworth & Pierrehumbert, 2013). A recent study of Goldblatt et al.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of greenhouse gas contents, such as CO 2 and CH 4 , is likely responsible for the FYSP (e.g., Wolf and Toon (2013); Byrne and Goldblatt (2014); Le Hir et al (2014)). Other factors or feedbacks may have also contributed to solving this problem, such as a different atmospheric pressure, a less continent coverage, N 2 -H 2 collision-induced warming, and a stronger tidal heating induced by the closer Moon (Goldblatt et al, 2009;Rosing et al, 2010;Goldblatt & Zahnle, 2011;Wordsworth & Pierrehumbert, 2013;Heller et al, 2021). A recent study of Goldblatt et al (2021) suggested that a long-term cloud feedback exists and it could also be a part of the solution to the FYSP.…”
Section: Introductionmentioning
confidence: 99%
“…Earth's moon is exceptionally important to human culture and the existence of life on Earth. Heller et al (2021) suggest that the moon's tidal pull produced enough heat to keep the early Earth's surface warm while the sun was not yet at its full radiative strength, and this helped contribute to some stability of the early Earth's climate. It is larger than other moons in our solar system proportional to the size of the planet.…”
Section: The Formation Of the Moonmentioning
confidence: 99%